HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA PUTRI TENTANG PENDEWASAAN USIA PERKAWINAN DI MA PONDOK PESANTREN TEKNOLOGI - RIKA ISTAWATI (Jurnal Ilmu Kebidanan, 2019)
Indonesia including the country the percentage of marriage at a young age the highest in the world ranked to thirty seven. The baby was born by early marriage also has the possibility of higher to born premature infants with low birth weight and malnutrition. Based on the initial survey on teenage girls in MA Pondok Pesantren Technology from 11 teenage girls, 8 people do not know about the age that secure to marry, and negative attitude to want to marry at a young age to avoid adultery, and 3 people know married at the age of < 20 years may be at risk of pregnancy. This research aims to know the knowledge with the attitude of the young girls about Maturation age of marriage on girls. The type of quantitative research analytically with the design of the c ross secsional. The population in this research were consists of 61 teenage girls and samples with total sampling. Data processing result from 61 respondents the majority of respondents had enough knowledge about Maturation age of marriage that consists of 25 people (40,0%), the majority of respondents negative attitude that consists of 41 people (67,2%). Based on the analysis of test chi square obtained the value p value 0.039 < α 0.05 which means that there are any significant relationships between the knowledge with the attitude of the young girls about Maturation age of marriage. To health workers is expected to increase the intensity of counseling and awareness about the dangers of early marriage and the spread about Maturation age of marriage.